2020
DOI: 10.1038/s41416-020-0809-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the small GTPase Ran by miR-802 modulates proliferation and metastasis in colorectal cancer cells

Abstract: Background The small GTPase Ran is upregulated in multiple cancers and fundamental for cancer cell survival and progression, but its significance and molecular mechanisms in colorectal cancer (CRC) remain elusive. Methods Ran expression was detected in CRC cell lines and tumour tissues. In vitro and in vivo functional assays were performed to examine the effects of Ran on cell proliferation and metastasis. The pathways and effectors regulated by Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Ran was reported to activate the EMT process and various metastasis-related signaling pathways, such as the Akt pathway, Ras pathway, and β-catenin pathway [ 20 , 21 ]. The oncogenic functions of Ran have been confirmed in colorectal cancer, breast cancer, ovarian cancer, and other solid tumors [ 22 25 ]. In GC, Ran was found upregulated and expected to be an immune recognition site molecule [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ran was reported to activate the EMT process and various metastasis-related signaling pathways, such as the Akt pathway, Ras pathway, and β-catenin pathway [ 20 , 21 ]. The oncogenic functions of Ran have been confirmed in colorectal cancer, breast cancer, ovarian cancer, and other solid tumors [ 22 25 ]. In GC, Ran was found upregulated and expected to be an immune recognition site molecule [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro experiments also further showed that miR-802 promoted the proliferation of lung cancer cells. 35 The abnormal expression of miR-802 has been confirmed in the tumor tissues or tumor cells of 15 cancers, including TSCC, 4 OSCC, 5,6 LSCC, 8 GC, [9][10][11] CRC, [12][13][14] PC, [30][31][32] HCC, [22][23][24][25] PCa, 2,33 bladder urothelial cancer, 26 BC, 15,16 CC, [17][18][19] EOC, 20 lung cancer, [34][35][36] osteosarcoma, 27,28 and melanoma. 21 To note, the abnormal expression of miR-802 in ESCC 7 and cholesteatoma 29 has only been confirmed in tumor cells.…”
Section: Ab Err Ant E Xpre Ss I On Of Mir-8 0in Tumor Smentioning
confidence: 99%
“…Subsequent experiments further revealed that miR-802 expression can regulate a series of cell behaviors, including cell proliferatio n, 2,[7][8][9]11,[13][14][15]18,[20][21][22][24][25][26]28,29,31,[33][34][35] invasion, 4,6,[11][12][13][14]17,[19][20][21]33,34,36 metastasis, 2,6,7,[11][12][13][14]17,20,21,25,26,33,34,36 apoptosis, [8][9][10]13,...…”
Section: Ab Err Ant E Xpre Ss I On Of Mir-8 0in Tumor Smentioning
confidence: 99%
See 2 more Smart Citations